Barriers facing Micro-encapsulated Phase Change Materials Slurry (MPCMS) in Photovoltaic Thermal (PV/T) application. (November 2020) - Ali, Samir; Mustafa, Mahmud
Abstract: Photovoltaic generation is a temperature-dependent technology, with each 1 °C temperature rise of the PV module, the efficiency drops by 0.2–0.5 % depending on the material of the PV cells. MPCM slurry is employed in the study to work as a cooling medium that circulates through a serpentine pipe to absorb heat from the back of a (0.8m x1.6m) 1.28 m 2 PV module for cooling purpose. The paper presents the experimental rig, the procedure of using MPCM slurry in PV/T and the limitations to its application. The experiments run under specific laboratory conditions with three concentrations of MPCM (5%, 10%, and 15%) in the slurry to test the effect of the major parameters such as radiation, Reynolds number and the concentration of the MPCM in the slurry on the performance of the system. The results showed that the system achieves 83% overall efficiency and 5.9 coefficient of performance (COP) when it operates with 10 % MPCM concentration slurry. Despite the good experimental outputs, the system is facing some problems that impede its application mostly due to the complexity of the cooling medium (MPCMS).